1982
DOI: 10.1007/bf00403727
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin treatment of psoriasis

Abstract: Somatostatin treatment was administered to 20 psoriatic patients according to the following protocol: Continuous infusion (250 micrograms/h) for at least 2 days followed either by short infusions (1 h) at 8 A.M. and 8 P.M. (12 cases) or by repeating the initial 2-day infusion (eight patients). Before treatment (day 0) and on day 6, biopsy specimens were taken for routine examination (12 patients) and for ultrastructure (seven patients). In vitro immunological studies were carried out on peripheral blood lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Weber et al [1] have observed elevated levels of GH in 70 psoriatic patients; somatostatin therapy was responsible for improvement or disappearance of the skin lesions in 22 out of 26 patients [2], Similar therapeutic results have been obtained by others [3][4][5]. However, other reports failed [6] or could not correlate raised plasma GH levels to demonstrate any variation in promoting psoriasis |7].…”
Section: Introductionsupporting
confidence: 47%
See 1 more Smart Citation
“…Weber et al [1] have observed elevated levels of GH in 70 psoriatic patients; somatostatin therapy was responsible for improvement or disappearance of the skin lesions in 22 out of 26 patients [2], Similar therapeutic results have been obtained by others [3][4][5]. However, other reports failed [6] or could not correlate raised plasma GH levels to demonstrate any variation in promoting psoriasis |7].…”
Section: Introductionsupporting
confidence: 47%
“…The role of GH in psoriasis was first raised by Weber et al [1|, who found increased plasma GH levels in 70 patients with psoriasis of all clinical forms. Moreover, GH levels were significantly higher in patients with extensive psoriasis; GH inhibitors (bromocriptin and somatostatin) were responsible for the clear ing of skin lesions [2][3][4][5]. Recently, Weber and Heitz [12] reported hyperplasia of GH-producing cells in the pitui tary glands of 12 postmortem patients with psoriasis, although there is no tendency to develop psoriasis in con ditions of inappropriate GH secretion as in acromegalic patients.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that SM-C /IG F-I is a strong candidate for mediating this process, and are currently investigating the differential production of SM -C/IGF-I by psoriatic and non-psoriatic fibroblasts. Since somatostatin inhibits SM -C/IGF-I production, this mechanism may also ex plain the therapeutic efficacy of som atosta tin infusion in psoriasis [24], To investigate the potential role of human growth hor mone in psoriasis, we have recently studied plasma levels of SM-C/IGF-1 in psoriatic patients, but have found no increase [25]. This result, however, does not negate the possible paracrine function of dermal fibroblast-derived SM -C/IGF-I on the epidermis [25].…”
Section: Discussionmentioning
confidence: 99%
“…I read with great interest the paper by Nickoloff et al [ 1 ] dealing with somatomedin C receptors on kératinocytes. In their discussion the authors quote our previous work on somatostatin treatment of psoriasis [2] arguing that the role of somatomedin C in psoriatic kératinocyte pro liferation could be sustained by 'the therapeutic efficacy o f somatostatin infusion in psoriasis'.…”
Section: Somatomedin Somatostatin and Psoriasismentioning
confidence: 99%